Transcrestal Maxillary Sinus Membrane Elevation using Osseodensification Compared with Alveolar Ridge Augmentation using the Lateral Window or Osteotome Technique: a Systematic Review and Meta-Analysis - Thomas Starch-Jensen; Kimie Bols Østergaard; Niels Henrik Bruun; Inleel Lundgaard Shino; Malene Halskov Hallund (eJournal of Oral Maxillofacial Research)
Objectives: The objective of the present systematic review was to test the hypothesis of no difference in implant outcome following transcrestal maxillary sinus membrane elevation using osseodensification compared with osteotome-mediated sinus floor elevation or maxillary sinus floor augmentation applying the lateral window technique.